METHODS FOR DOCUMENT IMAGE ANALYSIS BASED ON RETINEX THEORY AND ELLIPSE SHAPES - LABIB FARAG, MARIAN WAGDY (2014)
Conversion from gray scale or color document image into binary image is the main step in most of optical character recognition (OCR) systems and document analysis. After digitization, document images often suffer from poor contrast, noise, non-uniform lighting, and shadow. Also when a page of a book is digitized using a scanner or a camera, a border noise, which is an unwanted text coming from the adjacent page, may appear. The skew arises in the document due to incorrect placement or due to shifting of the object when the scanner lid is being closed. These problems may result in undesired results in OCR and document analysis. Document image cleanup is an active subject in image processing, which addresses these problems. In this thesis, we developed techniques of cleaning up and enhancing document images that suffer from problems resulting from the digitization process.